Envision it! Visual skills handbook : Reading Street Grade 4.1. - Foresman, Scott (United States : Pearson Education, 2011)
Author's purpose, Cause and effect, Classify and categorize, Compare and contrast, Draw conclusions, Fact and opinion, Generalize, Main idea and details, Graphic sources, Literary elements, Sequence, Steps in a process
Keywords: Reading-; Reading-study and teaching